A study on the improvements of learners studying TOEIC preparation classes at TiengAnh123 English center. M.A. Thesis Linguistics: 60 14 01 11 - Nguyễn, Thị Lựu (ĐHNN, 2017)
In recent time, there has been an increasing number of those who want to sit a TOEIC test to get a desirable score for their college graduation or job application in Vietnam. This has resulted in the fact that many English centers have included TOEIC preparation courses in their training program. These centers usually state strongly about the effectiveness of their TOEIC preparation classes; however, there has been little investigation on this so far. This study is intended to explore the improve ments made by TOEIC learners in terms of (1) their test - taking strategies, and (2) their test scores. The participants selected for the study included 43 learners from three TOEIC classes at TiengAnh123 English Center in Hanoi. Through the instruments of pre - and post tests and survey questionnaires for learners, the study discovered that after taking a 2 - month preparation course, the learners have significantly improved their TOEIC general and specific test - taking strategies. In addition, regarding TOEIC scores, on average, learners have made an increase of approximately 200 points with about 80 points for Reading section and 122 points for Listening Comprehension section